Atlas of PV Solar Systems Across Libyan Territory - Nassar, Yasser F.; El-Khozondar, Hala J.; Alsadi, Samer Y.; Abuhamoud, Nassir M.; Miskeen, Guzlan M. (2022 International Conference on Engineering & MIS (ICEMIS), 2022)
One of the most potential sources of renewable energy in Libya is solar energy. The temperature of the Solar PV module has a significant impact on its electrical output. Due to the size and diversity of the topography of Libya, meteorological conditions including temperature, wind, rain, and humidity vary greatly from region to region. As a result, this variation must be taken into account when evaluating the viability of PV solar module and inverter, taking into account the selection of the right PV technology in terms of the electrical characteristics, and avoiding extrapolating the findings of one location to the entire nation. The purpose of this research is to evaluate the performance of various PV technologies to determine whether they are suitable for use in Libya under various weather conditions. The research utilized the data provided by Solargis Database Company in analyzing the performance of PV solar field since weather data is not available. Key economic parameters of three different types of PV solar modules were simulated subject to real weather conditions of the considered sites using System Advisor Model software (SAM) simulation tool developed by the NREL-USA. The research determined the most suitable types of PV solar module and inverter for each zone across the Libyan territory with high accuracy. The obtained results can be implemented in the preliminary design stages, especially in the selection of the type of PV solar modules to be installed in a particular location, where a difference in the LCOE values up to 45% was remarked between several types of PV solar modules for the same location.